(untitled) (The Research of Medical Science Review, 2025)
Problem-based learning (PBL) is a student centered approach that shifts the role of the teacher to the student. It is based on self-directed learning. PBL has been adopted in undergraduate and postgraduate medical education and LBL is the traditional learning method. The lectures have limitations such as passivity boredom, large group size. In this study we compared both of these methods and recorded the preference of medical students. A cross sectional study was carried through convenience sampling and 180 responses were taken from medical students of 3rd year and above. The survey response rates were in the favour of PBL, the study results revealed that the experimental group was considered PBL is effective in their learning process PBL methodology obtained a high level of satisfaction, especially among students. It was more effective than other more traditional (or lecture-based methods) at improving social and communication skills, problem-solving and self-learning skills. Result: PBL is an effective and satisfactory methodology for medical education. It is likely that through PBL medical students will not only acquire knowledge but also other competencies that are needed in medical professionalism.